(untitled) (Bangladesh Medical Journal, 2019)
Primary dysmenorrhea refers to painful menstrual cramps of uterus led to considered gynecological complaint. Menstrual discomfort was reported in half to four-fifth of females and one-fourth reported sever dysmenorrhea. Newer combination of herbal products like Fennel and Mefenamic acid becoming popular and replacing conventional NSAIDs/ OCPs therapy for their major adverse effect. The aim of this study was to compare the effect of Mefenamic acid alone and combination with Fennel (Foenicullum Vulgare) on primary dysmenorrhoea. This interventional study was conducted among randomly selected 100 female workers with age range 18-25 years of two Garments Factories at Demra, Dhaka during July 2014 to June with the complaints of moderate to severe pain intensity and bleeding of primary dysmenorrhea. There were two group, group A (50 women) were treated with Cap Mefenamic Acid 250 mg once daily and group B (50) were with Cap Mefenamic Acid 250 mg once daily and fennel supplementation 10 ml three times daily. The mean age of respondents was 21.60 ± 2.59 and menarche age was 13.92±1.15 year. Mean duration of the menstrual cycle and cycle length were 6.24±1.66 and 27.36±3.63 days respectively. Mean onset age of Dysmenorrhea 16.16±1.81 year and intensity of dysmenorrhea (VAS-Visual Analogue Scale) 6.5±1.6. Group A had no any special experience on pain relief sensation by taking Mefenamic Acid alone, whereas Group B gathered better experience after administration of Cap Mefenamic Acid with fennel supplementation. Moreover, according to result of the analysis, comparison with bleeding tendency was also not shown the significant difference. One more important thing is that these two group faced some adverse effect of those medication such as group A had no complaints of allergic reaction, visual and neurologic disturbance where 2% had gastro-intestinal upset and 2% had respiratory distress in Group A; on the other hand, 2% had allergic reaction, 2% had visual symptom and respiratory distress had 4% cases in Group B. Mefenamic acid with fennel can decrease the severity of dysmenorrhea. However, any intervention might be found out to treat dysmenorrhea with less adverse effects is highly desired. Bangladesh Med J. 2019 May; 48 (2): 38-43